2012
DOI: 10.1111/j.1460-9592.2012.03841.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and parental presence during induction of anesthesia: an examination of the role of ethnicity and language

Abstract: Parental ethnicity and language may impact desire and motivation for PPIA, which may subsequently impact the effectiveness of PPIA and child anxiety at anesthesia induction. Future research should examine the impact of parental characteristics, including cultural variables, on children's preoperative anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Special mention should be made in parental presence at induction of anesthesia since it is a common practice in many countries although its benefits cannot be generalized internationally [ 22 ]. As Fortier et al [ 23 ] noted, parental cultural variables such as ethnicity and language may influence their desire for being present at induction of anesthesia and consequently the effectiveness of the intervention. To our knowledge, there is no recent evidence concerning Greek parent's desire for being present at their child's induction of anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Special mention should be made in parental presence at induction of anesthesia since it is a common practice in many countries although its benefits cannot be generalized internationally [ 22 ]. As Fortier et al [ 23 ] noted, parental cultural variables such as ethnicity and language may influence their desire for being present at induction of anesthesia and consequently the effectiveness of the intervention. To our knowledge, there is no recent evidence concerning Greek parent's desire for being present at their child's induction of anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…9 Specifically with regard to parental presence, both Spanish- and English-speaking Hispanic parents demonstrated a greater desire to be present for induction of anesthesia, but no evidence exists regarding beliefs and motivations regarding this practice. 10…”
Section: Fp For Pediatric Anesthesia Inductionsmentioning
confidence: 99%
“…9 Specifically with regard to parental presence, both Spanish-and English-speaking Hispanic parents demonstrated a greater desire to be present for induction of anesthesia, but no evidence exists regarding beliefs and motivations regarding this practice. 10 FP DURING CESAREAN DELIVERY Another helpful literature for evaluating FP in the OR regards the common practice of partner presence during labor and childbirth. Women have reported partner presence during childbirth to be an important form of support; and studies have shown the presence of partners during placement of neuraxial anesthesia to reduce patient anxiety, although other studies have shown no impact on maternal anxiety or pain with partner presence.…”
Section: Patient-and Family-centered Carementioning
confidence: 99%